Segmentation of consumers of honey and identification of honey preference in Kota Bengkulu - Selmi Selmi; Irnad Irnad; Sistanto Sistanto (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
As a country with a vast natural forest, Indonesia has a big potential production of honey. Honey is nutritious food produced by bees that mostly inhabit in the forest. Bengkulu is one of such place produced honey. Honey is considered as healthy supplement by consumer. Therefore, in this research, it has been studied the segmentation of consumers of honey and identification of honey attributes. This research was conducted in June- July 2015. There were 96 responsents gathered from eight (8) outlets selling honey products in Kota Bengkulu. Results showed that the consumers were young adults (67%), women (62%), married (82%), S1 education (56%), Kota Bengkulu domicile (88%) with income range of Rp 2,100,000-5,000,000/month (62%). While the preference testing of honey products based on taste, aroma, and color had the score around 3.5- 3.7. This meant that respondents like the honey product.